2005
DOI: 10.1002/asi.20222
|View full text |Cite
|
Sign up to set email alerts
|

Managing knowledge conflicts in an interorganizational project: A case study of the Infocomm Development Authority of Singapore

Abstract: As knowledge gains currency as a critical resource in the information-intensive economy, organizations have doubled their efforts to extract value from knowledge management endeavors, including the creation of interorganizational knowledge alliances. One particular aspect of such knowledge partnerships that has gone unnoticed in academic research is the presence of conflicts in knowledge activities. By adopting a conflict perspective of knowledge management in an interorganizational context, this study arrives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Automatically, such desires for conflict avoidance nurture a cordial atmosphere for interaction, which may nullified the role of interactional justice. But as rightfully pointed out by Lim and Tan [35], self-censorship behavior comprises the quality of knowledge contribution, which may become more of a hindrance to the fulfillment of psychological contracts as the deadline for solving the problem approaches [see also 60]. Arguably, as the project submission deadline looms, virtual project team members could be pressured to perform such that they are less conscientious of their reactions when communicating with others.…”
Section: Effect Of Interactional Justicementioning
confidence: 97%
See 2 more Smart Citations
“…Automatically, such desires for conflict avoidance nurture a cordial atmosphere for interaction, which may nullified the role of interactional justice. But as rightfully pointed out by Lim and Tan [35], self-censorship behavior comprises the quality of knowledge contribution, which may become more of a hindrance to the fulfillment of psychological contracts as the deadline for solving the problem approaches [see also 60]. Arguably, as the project submission deadline looms, virtual project team members could be pressured to perform such that they are less conscientious of their reactions when communicating with others.…”
Section: Effect Of Interactional Justicementioning
confidence: 97%
“…Lim and Tan [35] hinted at a logical explanation for this phenomenon in positing that individuals possess an intrinsic character of conflict avoidance to the extent to which participants collaborating on group-oriented tasks share a stronger preference for self-censorship behavior at initial phases of cooperation [see also 60]. Automatically, such desires for conflict avoidance nurture a cordial atmosphere for interaction, which may nullified the role of interactional justice.…”
Section: Effect Of Interactional Justicementioning
confidence: 97%
See 1 more Smart Citation
“…Concerning inter-organizational collaboration, scholars observed that exchange relations between separate yet interdependent organizations involve both formal and nonformal bargaining processes and often reflect the conflict that arises from the continuous interplay (Pruden 1969). Thus, working with other firm in not easy and indeed may be even more difficult because of a variety of inter-organizational conflicts (Connelly 2007), including incongruence of interests (Hardy and Phillips 1998), disputes of knowledge management (Tan et al 2005), emotional incompatibilities (Rose and Shohan 2004), etc. In line with this dilemma, managing conflict between stakeholders (for example, supplier and buyer) has become an extremely important topic of inquiry (Rose and Shohan 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Without the appropriate structures and incentives for learning, attribution error would contribute to defective practices persisting in the organization (Lyytinen & Robey, 1999), rendering it resistant to change. Worse still, project managers and group members may even learn to fail (Jones & Hughes, 2001;Pan, Pan, & Hsieh, 2006;Pan, Newell, Huang, & Galliers, in press;Tan, Pan, Lim, & Chan, 2005) in the long run. Against such a backdrop, we present an exploratory study of a project post-mortem for an abandoned electronic procurement (e-procurement) system project.…”
Section: Introductionmentioning
confidence: 97%